O funcionamento dos discursos a partir do Plano Municipal de Cultura de Chapecó : da leitura à produção de sentidos para a formação do cidadão - Bernardi, Grasieli Canelles (2012)
The discourse goes ahead from writing and speaking, it involves a subject that is part of an ideology and he speaks from a specific space because he has a history. From studies about Discourse Analysis (DA) and the participation (literature articulator) in the elaboration of Chapecó Municipal Plan of Culture (CMPC), it is searched by a discursive analysis of cultural representations, through different areas. It is intent to observe the discourses (reading gestures) of some areas to the contribution of CMPC, to relate with DA and try to comprehend different effects of meaning about the representation of culture presented in the interviews and/or documents from different areas of PMCC. It will be searched some concepts concern the culture universe as its areas; it will be investigated if the development of the Plan produce representation of Chapecó Culture. It will be organized some discursive sequences which refer to Chapecó Culture from an interview (written questions); It will be cut a specific corpus (conception of culture, literature, reading, historical patrimony and contributions to the Plan) to analysis from some sequences; it will be emphasized some interpretative gestures, cultural representation in terms of linguistics and discourse to find the theory of AD. The final considerations are about possible contributions to the applicability of the discussed document